Automation of Forks-Conveyor System using Integrated Photodiode Sensor - Ricky Sinaga; Lanny W. Pandjaitan; Lukas Lukas (International Journal of Engineering Continuity, 2025)
Desynchronization between incoming containers and lifting forks prior to the starwheel is a common source of misalignment, container drops, and excessive mechanical load in 19-L bottled water filling lines. This study proposes a low-cost retrofit system that integrates a photodiode sensor with timer–relay logic to regulate start–stop motor control based on the real-time fork position. The system was implemented upstream of the filling station and evaluated during a three-week trial in an operating commercial facility. Results showed that the intervention reduced average starwheel load from 7.54 kg to 2.30 kg and decreased container-fall incidents by approximately 50%. In addition, the modification eliminated the need for one operator per shift, corresponding to annual labor savings of more than IDR 150 million and a payback period of less than one month. These findings demonstrate that photodiode-based synchronization can provide an industry-validated, cost-effective retrofit solution for packaging operations without the requirement for PLC reprogramming or major structural modification. Future work will address long-term durability, adaptability to different container geometries, and the potential integration of feedback and monitoring functions.